Case report: Goiter and overt hypothyroidism in an iodine-deficient toddler on soy milk and hypoallergenic diet - Caprio, Angela Maria; Umano, Giuseppina Rosaria; Luongo, Caterina; Aiello, Francesca; Dello Iacono, Iride; Palumbo, Stefania; Miraglia del Giudice, Emanuele; Grandone, Anna (Frontiers in Endocrinology, 2022)
Soy-based infant formulas (SF) are often consumed by cow’s milk allergic children. However, some concerns have risen since soy intake may adversely affect thyroid function in iodine-deficient or subclinical hypothyroid individuals. We report the first Italian case of SF induced goiter and hypothyroidism registered in our country since National Iodine program has been instituted. Finally, we review cases previously reported in literature. A 22-months-old toddler with a previous diagnosis of cow-milk protein allergy came to clinical attention for important goiter and overt hypothyroidism. Detailed dietary anamnesis revealed he was on a restrictive dietary regimen based on soy-milk since 12 months of age. A temporary levothyroxine substitution was instituted to avoid hypothyroidism complications. Adequate iodine supplementation and diet diversification completely reversed SF induced hypothyroidism and goiter, confirming the diagnostic suspicion of soy-milk induced thyroid dysfunction in a iodine deficient toddler. This case report demonstrates the importance of careful dietary habits investigation and adequate micronutrients supplementation in children on a restrictive diet due to multiple food allergies in order to prevent nutritional deficits.